The Effect of Tax Planning on Business Profitability with Tax Efficiency as a Moderating Variable (Study of Coal Energy Companies in the 2022 - 2024 Period) - Anichah Isma Ardani; Khasanah Sahara; Siti Isnaniati (LP2M IAIN Palopo, 2026)
This study aims to examine the effect of tax planning on firm profitability and to analyze the moderating role of tax efficiency in the relationship between tax planning and profitability in coal energy sector companies. This sector is characterized by relatively high profits, resulting in substantial income tax obligations, which encourage companies to implement tax planning strategies and improve tax efficiency to maintain financial performance. This research employs a quantitative approach using panel data from three coal companies listed on the Indonesia Stock Exchange, namely PT Adaro Energy Indonesia Tbk, PT Bukit Asam Tbk, and PT Indo Tambangraya Megah Tbk, covering the period of 2022 - 2024. Data analysis is conducted using Moderated Regression Analysis (MRA) after passing classical assumption tests. The findings indicate that tax planning has no significant effect on profitability, and tax efficiency also does not significantly influence profitability. Furthermore, tax efficiency is not proven to moderate the relationship between tax planning and profitability. This study contributes to the literature by providing empirical evidence on the moderating role of tax efficiency in the coal energy sector, which remains underexplored in the Indonesian context.